Development of a Model for Mitigating Fire Spread in Multi-Storey Buildings - Oluseyi, P.O.; Akinbulire, T.O.; Atunbi, C.T.; Akinyemi, M.I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In the developing nations that are located in the tropical region; there is a growing trend of fire incidence in buildings without adequate development of fire prevention and/or reduction protocol. Thus, this study addresses the growth and spread of fire in multi-storey buildings. The rooms are structured as cells in order to reduce the flame spread from a single fuel item, by heat release, to other neighbouring items or rooms (otherwise known as cells). The philosophy is to reduce the advent of vertical and horizontal fire spread. Thus, the mathematical model for the spread of fire in buildings over a solid fuel surface is therefore developed using the adaptation, development and simulation of cellular automata (CA) discrete model. The von Neumann neighbourhood cell configuration is adopted. Hence, the surface of the fuel is analysed using a regular square array (i.e. cells), while the flame spread is depicted as a series of ignitions of surface elements. In which case, ignition of an element is evaluated by a combination of critical surface ignition temperature and cellular automata discrete techniques. The work displays the movement of fire, from its origin of ignition to other fuel igniting elements around it. Consequently, this spread to other parts of the building. However, the technique presented in this work attempts to reduce the rate of growth of the fire spread using the predictive fire growth probability approach. In other words, the application of the cellular automata, using a multi-storey building, is herein presented. The study has potential to advance knowledge of technical approach to stop fire spread in multi-storey building. Thus it improves fire risk management as well as reducing magnitude of fire disaster and losses in the multi-storey buildings.